Disproportionality analysis of quinolone safety in children using data from the FDA adverse event reporting system (FAERS) - Kong, Wenqiang; Mao, Wei; Zhang, Lin; Wu, Yanyan (Frontiers in Pediatrics, 2023)
Background Quinolones are widely prescribed for the treatment or prevention of infectious diseases in children. To gain further insight into quinolone-associated adverse event (AE) in children and better protect pediatric patients, continued surveillance of safety data is essential. The purpose of this study was to characterize the safety profiles of quinolone-associated AEs in children by mining the FDA adverse event reporting system (FAERS). Methods FAERS reports from quarter 1 of 2004 to quarter 1 of 2022 were included in the study. The Medical Dictionary for Regulatory Activities (MedDRA) was used to identify adverse events. Reporting odds ratios (ROR) corresponding 95% confidence intervals (CIs) and information component (IC) along with 95% CIs were calculated to detect drug–AE pairs with higher-than-expected reporting rates within the FAERS from System Organ Classes (SOCs) to Preferred Terms (PTs). Reports were considered as signals if the 95% conﬁdence interval did not contain the null value. Results After inclusion criteria were applied, a total of 4,704 reports associated with quinolones were considered. Most FAERS reports associated with ciprofloxacin (N = 2,706) followed by levofloxacin (N = 1,191), moxifloxacin (N = 375), oflaxacin (N = 245) and ozenoxacin (N = 187). The most common age group was 12–18 years. The median weight was 39.0 kilogram. The adverse effects of quinolones emerging for SOCs primarily included Infections and infestations, gastrointestinal symptoms, blood and lymphatic system disorders, cardiac disorders, nervous system disorders, musculoskeletal and connective tissue disorders and psychiatric disorders. The most frequently AE signals at the PT level were pyrexia (N = 236), febrile neutropenia (N = 120), off label use (N = 48), drug resistance (N = 18) and cardiac arrest (N = 22) following the use of ciprofloxacin, levofloxacin, moxifloxacin, ofloxacin, and ozenoxacin, respectively. Serious oznoxacin-associated AE signals were found and have not been documented in the package insert. They included cardiac arrest (N = 22; ROR = 19.83; IC = 3.68), overdose (N = 21; ROR = 4.98; IC = 2.07), seizure (N = 16; ROR = 6.01; IC = 2.29), small for dates baby (N = 9; ROR = 14.7; IC = 3.05), completed suicide (N = 15, ROR = 18.87; IC = 3.51), asthma (N = 9; ROR = 6.69; IC = 2.24;) and hypotension (N = 9; ROR = 3.83; IC = 1.68). Conclusion This study provided additional evidence with respect to quinolones-related AEs for children. Generally, the findings of this study are compatible with AEs recorded in package inserts. The unexpected signals of ozenoxacin justify active vigilance by clinicians and timely monitoring by pharmacovigilance experts.